Introduction: On Police Violence and Systemic Islamophobia - Meziane, Mohamad Amer (Political theology, 2021)
This short essay examines the interdependence between the secular policing of Muslims and the policing of the entire population, between the policing of a racialized religion and the kind of bio-politics that control and surveil the entire population. During the pandemic, the former legitimizes the power and intensifies the arbitrariness of the latter. There is little doubt that this interdependence between policing Muslims – as well as brown and black bodies – and policing per se is at stake in the emergence of what might be seen as a new form of authoritarian police state in Europe and elsewhere. Through the French concept of separatism, race and political theology are thus entwined in such a way that their very distinction seems to vanish as an arbitrary convention that stems from the limitations of analytical thought.